Pendugaan Umur Simpan Cabai Bubuk Fermentasi dari Cabai Rawit (Capsicum frutences L.) dan Cabai Merah (Capsicum annuum L.) Menggunakan Metode Akselerasi Pendekatan Labuza - Bilang, Mariyati; Laga, Amran; ,, Trinoviyani . (REKAPANGAN, 2017)
ABSTRACT The aim of this research was to determine the shelf life of pepper powders derived from cayenne and red pepper fermented spontaneously. The pepper powders packed with plastic sac of HDPE (High Density Poly Ethelene) type then predicted their shelf life using acceleration method based on Labuza Aprroach. This research was devided into two stages: a preliminary and the main research; fermentation of pepper, dried of fermented pepper, and pulverization, followed by main research to predict the shelf life fermented pepper powders with accelerated method based on the Labuza equation wich was into derived from data of initial moisture content, critical water content, then determined of sorption isotherm curve, also the parameters supporting to predict of shelf life. Based on the results of sorption isotherm curve, that the lowest value of Mean Relatif Deviation (MRD) indicated the appropriate equation obtained for two peppers (Cayenne and red pepper powders) were Hasley and Caurie equation with value of MRD respectively 4,70 and 2,34. Based on the results of organoleptic test (hedonic test), shows that the aroma was not accepted at 76 days for fermented of cayenne powder and 52 days for fermented of red pepper powder, that indicated the critical water content of pepper powders (0,098 g H2O/g solid for cayenne powder and 0,132 H2O/g solid for red pepper powder). Plotting the value of the water activity (Aw) to equilibrium moisture content obtained from seven chambers with different range of RH (7-90%) acquired sorption isotherm curves for both types of pepper powders. Entering of all the measured parameters (initial moisture content, critical moisture content, permeability plastic sac as packaging, dry weight, and the saturated vapor pressure) into the Labuza equation then acquired the shelf life of fermented cayenne and red pepper powders were 78 days (2,6 months) and 62 days (2,1 months) respectively. Key words : Chili, Fermentation, Acceleration, Labuza